Динамiка коагуляційної та фібринолітичної ланок системи гемостазу і фібринолізу в хворих на гіпертонічну хворобу в процесі лікування периндоприлом i бiсопрололом - Морозова, О. В.; Морозова, Оксана Валентинівна; Morozova, O. V. (My University, 2015)
У 35 хворих на гіпертонічну хворобу І-ІІ ступеня вивчено вплив периндоприлу і бісопрололу на активність антикоагулянтних і фібринолітичних факторів плазми крові. Встановлено, що поєднання периндоприлу з бісопрололом істотно підвищує антикоагулянтну та фібринолітичну функцію ендотелію за рахунок активації протеїну С і антитромбіну ІІІ та пригнічення активності плазміногену і зниження вмісту інгібітора активатора плазміногена. Отже, гіпертонічна хвороба супроводжується розвитком ендотеліальної дисфункції, яка проявляється зростанням коагулянтних та пригніченням фібринолітичних властивостей плазми крові. Курсове лікування периндоприлом і бісопрололом сприяє збільшенню антикоагулянтного та фібринолітичного потенціалу плазмі крові. У 35 больных гипертонической болезнью І и II степени изучено влияние периндоприла и бисопролола на активность антикоагулянтной и фибринолитической активности плазмы крови. Показано, что сочетание периндоприла в с бисопрололом существенно повышает антикоагулянтную и фибринолитическую функцию эндотелия за счет активации протеина С и антитромбина III, угнетает активность плазминогена и снижает содержание ингибитора активатора плазминогена-1. Таким образом, гипертоническая болезнь сопровождается развитием эндотелиальной дисфункции, которая проявляется ростом коагулянтных и угнетением фибринолитических свойств плазмы крови. Курсовое лечение периндоприлом и бисопрололом способствует увеличению антикоагулянтного и фибринолитического потенциала крови. The study of the influence of perindopril and bisoprolol to the anticoagulative and fibrinolitic activity of plasma was carried out in 35 patients with hypertension I-II. The study have shown the perindopril in combination with bisoprolol significantly increases the anticoagulative and fibrinolytic function of endothelium due to activation of protein C and antitrombin III, and inhibits the plasminogen activity and decreases the plasminogen's-1 activator's inhibitor's level. Thus, hypertension is accompanied with endothelial disfunction development, which is manifested with the growth of anticoagulative features and depression of fibrinolytic features of blood plasma. Administration of course treatment with perindopril and bisoprolol leads to increase of anticoagulative and fibrinolytic blood potential. The main purpose was to study the influence of perindopril and bisoprolol to the anticoagulative and fibrinolitic activity in patients with hypertension. 35 patient with hypertension were observed. Among them, there were 15 patients with hypertenstion I and 20 patients with hypertension II. Perindopril was prescribed once a day in 4-8 mg dose. In case of its inadequate effectivity bisoprolol in dose of 10 mg a day was added into treatment complex. Treatment course was 6 months. In order to control there was examined a group of 30 healthy men. Before and after common venoocclusive test the blood was taken for determining of protein C, antitrombin III plasminogen tissue activator inhibitor-1 (PTAI-1) and plasminogen blood activity. Conclusions. Hypertension is accompanied with endothelial disfunction development, which is manifested with the growth of anticoagulative features and depression of fibrinolytic features of blood plasma. Administration of course treatment with perindopril and bisoprolol leads to increase of anticoagulative and fibrinolytic blood potential.
Динамика коагуляционного и фибринолитического звеньев системы гемостаза и фибринолиза у больных гипертонической болезнью в процессе лечения периндоприлом и бисопрололом
Dynamics of coagulative and fibrinolytic parts of the system of hemostasis and fibrinolysis in patients with hypertension during treatment with perindopril and bisoprolol
Keywords: гіпертонічна хвороба; антикоагулянтні та фібринолітичні фактори; периндоприл; бісопролол; гипертоническая болезнь; антикоагулянтные и фибринолитические факторы; периндоприл; бисопролол; hypertension; anticoagulants and fibrinolysis factors; perindopril; bisoprolol